Communicative Activity of Public Administration Bodies in the Conditions of Decentralization of Power in Ukraine - Korotych, O.V. (Theory and Practice of Public Administration, 2019)
In the process of decentralization of public authorities in Ukraine by means of creation of financially capable and self-developing agglomerated territorial communities by combining village and settlement communities it becomes impossible to establish fruitful cooperation with public authorities of other regions of the country, the public, international partners due to the lack of communicative competence of personnel and lack of experience in the implementation of effective communicative activities on behalf of public administration that is responsible for the socio-economic development of a large territorial complex. However, it should be noted that the communicative activity of many bodies of public administration at rayon, oblast and even central level is also carried out insufficiently due to the lack of a clear idea of its content, principles and approaches to its implementation. In order for the communicative activities of the public administration bodies to be effective, attention should be paid to the fact that, unlike communication, which is a process of interaction and information exchange, communicative activities are purposeful activities aimed to ensure the conditions for the implementation of the communicative process, increase its efficiency, enable feedback, analyze the effectiveness of communications and develop measures to improve further communicative actions (communication processes and individual actions they are made up of). At the same time, establishment of internal communications is not a communicative activity of public administration (this is the communicative activity of its structural subdivisions or employees of this body), therefore its main directions are to ensure effective public relations and fruitful interaction with other public administration bodies of particular importance in the course of the reform of public administration system on the basis of decentralization. At the same time, communicative activity of public administration bodies is directly carried out by particular officials of these bodies; therefore, special attention must be paid to the enhancement of communicative competence and the effectiveness of communicative activities of public servants, which directly affect the quality of public management services, the interaction of structural units of public authorities, cooperation of the authorities of different levels and systems in the process of management of socio-economic development of the territorial systems, as well as the relationship between public administration bodies and the public.